Prognostic Factors in Thyroid Papillary Microcarcinoma - Sezgin Zeren; Gizem Akkaş Akgün (Journal of Contemporary Medicine, 2023)
Aim: Our aim in this retrospective study is to evaluate the factors that are important in the prognosis of thyroid papillary microcarcinoma.